A comparative study of microRNAs in different stages of Eimeria tenella - Zhang, Lei; Chen, Linlin; Zhang, Hongtao; Si, Hongbin; Liu, Xianyong; Suo, Xun; Hu, Dandan (Frontiers in Veterinary Science, 2022)
Apicomplexan parasites have divergent situations in terms of small RNA generation. Analysis has shown that parasites in Plasmodium and Cryptosporidium as well as many species in Leishmania or Trypanosome do not have a complete machinery in small RNA biogenesis. Recently, the miRNA-generating system of Toxoplasma has been identified as plant/fungal-like and its miRNAome has been elucidated. However, nothing is known about Eimeria miRNAs. In this study, we characterized the RNA silencing machinery of E. tenella and investigated the miRNA population distribution at different life stages by high-throughput sequencing. We characterized the expression of miRNAs in the unsporulated oocyst, sporulated oocyst and schizogony stages, obtaining a total of 392 miRNAs. We identified 58 differentially expressed miRNAs between US and SO that were significantly enriched for their potential target genes in the regulation of gene expression and chromatin binding, suggesting an epigenetic modulation of these miRNA. In comparing miRNA expression at endogenous and exogenous developmental stages, twenty-four miRNAs were identified, mainly associated with protein kinase activities. This is the first study of Eimeria miRNAs and will provide basic knowledge for further studies to unveil the regulatory role of miRNAs in apicomplexan parasites.